2009
DOI: 10.1115/1.4000197
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of Hydraulically Expanded Tube-to-Tubesheet Joints With Linear Strain Hardening Material Behavior

Abstract: The mechanism of failure of tube-to-tubesheet joints is related to the level of stresses produced in the tube expansion and transition zones during the expansion process. Maintaining a lower bound limit of the initial residual contact pressure over the lifetime of the expanded joint is a key solution to a leak free joint. An accurate model that estimates these stresses can be a useful tool to the design engineer to select the proper material geometry combination in conjunction with the required expansion press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Sawczuck and Hodge’s comparative study in 1960 on yield conditions for circular cylindrical shells under axisymmetric radial pressure initiated a series of investigations [ 7 ]. The expansion process impacts four zones: residual stress, contact, transition, and unexpanded zones [ 8 ]. These zones, especially those undergoing work hardening and experiencing stresses beyond yield, warrant closer examination.…”
Section: Introductionmentioning
confidence: 99%
“…Sawczuck and Hodge’s comparative study in 1960 on yield conditions for circular cylindrical shells under axisymmetric radial pressure initiated a series of investigations [ 7 ]. The expansion process impacts four zones: residual stress, contact, transition, and unexpanded zones [ 8 ]. These zones, especially those undergoing work hardening and experiencing stresses beyond yield, warrant closer examination.…”
Section: Introductionmentioning
confidence: 99%
“…Before finite element analysis, it is important to determine material properties such as yield stress [ 13 ]. Previous studies have shown that strain hardening is an important factor influencing the accuracy of joint numerical analysis results [ 14 , 15 ]. Previous studies mainly focused on the combination of a carbon steel tube and low-alloy steel tube sheet, or the combination of a titanium tube and single-material tube sheet.…”
Section: Introductionmentioning
confidence: 99%
“…If the expansion pressure Pe being at its maximum value Pe_max, any pressure decrease beyond this value involves the simultaneous elastic recovery of the tube and the tubesheet. The contact pressure is obtained by analyzing the change in the radial displacement at their interface of the tube and tubesheet both treated as thick cylinders subjected to elasto-plastic deformation with linear strain hardening (Laghzale and Bouzid, 2009b). The change of displacement during the release of expansion pressure must be the same such that:…”
Section: Expansion Without Tubesheet Plastic Deformationmentioning
confidence: 99%